A Model for the Rice and Wheat Economy in Malaysia: An Empirical Assessment of Alternative Specifications - Baharumshah, Ahmad Zubaidi (1989)
A model of the Malaysian rice and wheat economy is specified and fitted to data from 1960-87. Several diagnostic tests were employed in the analysis to determine the specification of the model. The present work incorporates the interaction between rice and wheat. The estimate for the short-run supply price elasticity is 0.03 while the long-run price elasticity is estimated at 0.11. The matrix of price and income elasticities obtained from the demand analysis indicates that the own-price elasticities are less than unity. The present work supports the hypothesis that rice is an inferior good while wheat is normal. The leVel of imports depends on domestic supply, income level and domestic prices of rice and wheat.